2013
DOI: 10.5455/vetworld.2013.27-30
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological evaluation of packaged bottled water sold at Jaipur city and its public health significance

Abstract: Aim: The study was carried out to investigate the microbiological quality of packaged drinking water marketed in Jaipur city. Material and Methods:In the present study 'twenty' drinking water samples (15 water bottles and 5 sachets) of different brands purchased randomly, were evaluated to access the water quality on the basis of different bacteriological parameters.Result: Out of twenty, 50% samples were found unsatisfactory in standard plate count. Psychrophillic, coliforms, E. coli and staphylococcal counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 3 publications
2
49
0
Order By: Relevance
“…Microbial evaluation of all water samples revealed high levels of total coliform bacteria in the sachets but not in the bottles. Similar results were found in studies done by Gangil R et al, [11], Majumder AK et al, [31], Semerjian L [10], Urvashi et al, [32], Zeenat et al, [33] and Ajayi AA [34]. The microbial contamination of packaged drinking water could be influenced by factors such as their raw water sources, treatment processes which were employed and hygienic practices which were observed in their productions.…”
Section: Samplingsupporting
confidence: 77%
See 2 more Smart Citations
“…Microbial evaluation of all water samples revealed high levels of total coliform bacteria in the sachets but not in the bottles. Similar results were found in studies done by Gangil R et al, [11], Majumder AK et al, [31], Semerjian L [10], Urvashi et al, [32], Zeenat et al, [33] and Ajayi AA [34]. The microbial contamination of packaged drinking water could be influenced by factors such as their raw water sources, treatment processes which were employed and hygienic practices which were observed in their productions.…”
Section: Samplingsupporting
confidence: 77%
“…Contrary results were found in the study [4] 114 have shown that qualities of the bottled water in different countries were within acceptable range. But due to influx of a large number of local brands and administrative ignorance, the physical, chemical and bacteriological quality parameters of packaged water sources have not been found to be in the acceptable limits, in the studies which were conducted by Gargil R et al, [11], Oyelude and Ahenkorah [21], Ackah M et al, [22] and Kwakye-Nuako et al, [23].…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of E. coli in chevon meat samples recorded was 38.09%, which is in agreement with earlier findings (Ali et al, 2010). However higher prevalence rates of 57% (Amin and Borah, 2002), 76% (Gangil et al, 2011) and 100% (Chaubey et al, 2004) were reported by different investigators. In present study, 20.19% milk samples were found positive for E. coli, however higher prevalence rates of 33.96% (Rashid et al, 2013), 38% (Thaker et al, 2012) and 43.3% (Rasheed et al, 2014) were reported from different regions.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that packaged water can be contaminated with bacteria at various stages of production [18][19]. Under improper or prolonged storage of bottled water, bacteria can grow to levels that may be harmful to human health [10].…”
Section: Introductionmentioning
confidence: 99%